Perception of Green Roof and Flat Roof Development in High-Rise Building in Malaysia - Nur Syazanna Iryani Binti Abd Razak; Dr Ali Tighnavard Balasbaneh (Recent Trends in Civil Engineering and Built Environment, 2022)
The environmental impact of construction activities occurs from the initial work stages to the construction period, operational period, and the final demolition when a building comes to the end of its life. In order to make sure the construction activity can be run in line with considering the environmental health, green roofs are very relevant to Malaysia which is now experiencing rapid urbanization and loss of green areas in most of its major cities. On the other hand, flat roofs have a wide application in many countries, following the architectural evolution, the emergence of new materials, and the improvement in the performance of the existing ones. With the norm of the flat roof application in the building industry, it has become way challenging in persuading building owners to take a turn from a flat roof to a green roof for the construction of their building. This study focuses on the perception of building industry players such as developers (owners), architects, consultants, engineers, and contractors of the advantages and disadvantages of green and flat roofs system in the construction of high-rise buildings in Malaysia. A questionnaire was distributed to the local building sector in order to fulfill the objectives of the study which are to identify the advantages and disadvantages of green and flat roofs that concern the construction practitioners, to analyze the barriers of the green roof development, and to provide strategies to enhance the implementation of green roof in Malaysia’s construction industry. Data from the questionnaire then extracted into SPSS and some analysis has been taken into account (frequency analysis, mean analysis, standard analysis, and percentage analysis). Based on the results, respondents found that the most benefit of green roof is it offer healing environments and the most disadvantages of green roofs are limited of roofing materials, skilled labors and professional team required, high consideration of structure, and high installation and construction initial cost. Although the pros of green roofs outweigh the cons, the development and implementation of green in Malaysia are still slow and this needs to be changed for the sake of our environmental health.